Pengaruh Komite Audit Dan Dewan Pengawas Syariah Terhadap Earnings Management Perbankan Syariah Di Indonesia Tahun 2018 – 2022 - Wahyuni Wahyuni; Sri Ramadhani; Nuri Aslami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this research is so that we can find out whether there is an influence of the audit committee and sharia supervisory board on earnings management. The research method uses a quantitative approach with the use of secondary data processed through the SPSS Version 25 software system. The results of the test prove whether the audit committee partially has no effect on earnings management in sharia banking. This is shown from the results of the t test in table 4.8, which shows that the calculated t value in the audit committee is -0.907 and a significance level of 0.369. With a tcount value (-0.907) < ttable (1.672) and a significant value (0.369) > 0.05. Partially, the sharia supervisory board has no influence on earnings management in sharia banking. This is shown from the results of the t test in table 4.8. The calculated t value for the sharia supervisory board is 1.007 and the degree of significance is 0.320. With a tcount value (1.007) < ttable (1.672) and a significant value (0.320) > 0.05. Simultaneously the audit committee and sharia supervisory board have no influence on earnings management in sharia banking. This is reinforced by the results of the F test in table 4.9. The calculated F value for the audit committee and sharia supervisory board is 0.767 with a significance level of 0.470. With a value of Fcount (0.767) < Ftable (3.159) with a significance value of (0.470) > 0.05. So it can be concluded that the audit committee has no effect on earnings management and the sharia supervisory board has no effect on earnings management and the audit committee and sharia supervisory board have an effect on the profitability of earnings management.